KARAKTERISTIK BEBERAPA MINYAK ATSIRI FAMILI ZINGIBERACEAE DALAM PERDAGANGAN - Ma’mun Ma’mun (Buletin Penelitian Tanaman Rempah dan Obat, 2006)
Characteristics of Saveral Essential Oils of Zingiberaceae Family Plant in TradeThe essential oils of zingiberaceae such as cardamom oil, ginger oil and cur-cuma oil used in medicin, parfum, food and beverage industries and aromatheraphy. Cardamom oil is distilled of E. Cardamo-mum, produced in India and Sri Langka. Ginger oil (G. officinale) comes from Cina and India. Meanwhile curcuma oil (C. Xan-thorrhiza) is still used in domestic and limi-ted scale. The identification of characteristic of cardamom oil, ginger oil and curcuma oil originated from West Java, Central Java, Lampung and some eksporters was conduc-ted in the Post harvest technology labora-tory, Research Institute for Spice and Med-icinal Crops. The essential oils distilled using water and steam distillation methode. Oils obtained were analyzed to get the oil characteristics which discribed in specific gravity, refractive index, optical rotation, solubility in ethanol, acid number and ester number. The characteristics of those essen-tial oils was compared to the Inetrnational Standard. The result showed that the oil cha-racteristics of A. cardamomum and E. Car-damomum is very different. But the oil cha-racteristics  of E. Cardamomum from West Java and Indonesian exporter is the same to the international standard specification. Characteristics of ginger oil from Central Java, Lampung and Indonesian exporter is not agree with international standard espe-cially in optical rotation specification.